(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
شكّل النصّ القرآني من حيث هو رسالة سماوية، بناء تبليغياً وفق قواعد اتّصاليّة ,فخاطب وحاور الآخر، ونال القرآن الكريم قسطاً كبيراً من الدراسة والتحليل. فلم تبق منه ظاهرة إلا وتعرّض إليها العلماء والباحثون ـ قدامى ومعاصرون ـ في هذا الكتاب العزيز. ولكن كلما درسنا النص القرآني من جانب مختلف، كشفنا وجوها عدة جديدة. .فكانت ظاهرة الاتصال فيه، مفتوحة على شؤون الناس، وما يخصّ تجددها وتطورها الدائم، متخذاً الإقناع سبيلا يسلكها في استقطاب الناس نحو الإسلام. فالقرآن الكريم جاء ليسطر علاقته مع خالقه ونفسه وغيره من البشر. فهو رسالة موجهة إلى البشرية جمعاء، يُعتمد فيها على مخاطبة العقل في عملية الإقناع، مقدما ً بذلك لغة حية تصلح لكل العصور لها دور فعال في إقناع الآخرين، هي في أساسها موجهة من أجل التأثير على آراء المخاطب وسلوكياته واستمالة العقل، وفق استراتيجية لغوية خاصة، تقوم على أساس توظيف اللغة داخل بنية متجددة، ترتبط بالمتكلم والمتلقي داخل سياق اجتماعي ونفسي واتصالي محدد، غايتها تتمثل في التأثير بالمتلقي. وفي عملنا هذا نتعرض إلى سورة مريم، التي تشكل قدراً كبيراً من الأهمية في الدراسة اللغوية، وفيها مخاطبة الناس ووعظ ومجادلة ومناظرة، إضافة إلى طريقة خاصة في إقامة الحجة والبرهان والاستدلال. إن النصّ القرآني، لا يقصّ قصة إلا ليواجه بها واقعاً، ولا يقرر حقيقة إلا ليغير بها باطلا، وهي الغاية الأسمى في الاتصال، إذ يحاول المتكلم التأثير في الآخر وجعله يقتنع بالطرح الجديد، فيتوصل إلى التأثير على الطرف الآخر الجديد، وبالتالي يلزمه الحجة معتمداً على قصص الأنبياء والمرسلين الذين أرسلوا إلى الأمم السابقة. ومن هنا برزت أهمية البحث بوصفه موضوعا من الموضوعات العلمية، المتصلة بأشرف كتاب في هذا الوجود، ألا وهو القرآن الكريم. ذلك أن الاتصال ارتقى لأن يكون علماً من أهم العلوم اللسانية برمتها، بالإضافة إلى تقصي الظواهر في القرآن الكريم ومحاولة الكشف عن أغوارها عن طريق إثباتات مؤسسة على نظريات علمية حديثة، تبحث في علم أصيل له أسس وضوابط مختلفة وكل ذلك من خلال القرآن الكريم. وقد اخترت المضامين الاتصالية والإخبارية في سورة مريم موضوعا للدراسة بسبب جدته في الدراسات العربية المعاصرة، في جانبها النظري ومحدودية الدراسات التطبيقية في مجال التحليل القرآني. The Quranic text ,through being a divine message , formed a messaging structure according to communication rules so it talked and contacted the other and got a great deal of study and analysis . So scientists and researchers , veterans and contemporary , studied all the phenomena in this valuable book. The more we study the Quranic text from different side , the more uncovered faces we find. For example , the phenomenon of communication was opened to the situations of people and everything related to their permanent renewal and development , taking persuasion in a way to attract people towards Islam. The Quran came to underscore his relationship with the Creator and itself and other people . It’s a message addressed to all humanity , depends in which to address the mind in the process of persuasion , offering a living language suitable for all ages , has an effective role in persuading others , essentially forwarded to influence the views of the addressee , swaying the mind according to a specific linguistic strategy based on the employment of language within renewed structure linked ideologue and the receiver within a social and psychological context with the purpose of influencing the recipient. The Quranic Text tells stories for facing reality and does not decide the truth , but to change void, which is the supreme goal of communication where speaker tries to effect the other and makes him convinced with the new offer and gets the answer to influence the other new party , therefore forces the argument relying on stories of the prophets and messengers who were sent to previous nations. Hence the importance of research rises as one of the scientific subjects that connects to the clearest book in the world, which is Quran. The connection is elevated to be informed of the most important linguistic science as a whole . As well as investigating the phenomena in the Quran and trying to detect underneath by evidence based on modern scientific theories , you are searching through a science of foundations and different control rules all through Quran.I have chosen Informative & Communicative Tenors in the story of Meriam as a subject of study because it’s a new research in Contemporary Arab Studies in theoretical part and limitations of empirical studies in the field of Quran analysis .